Penerapan Health Promotion dan Education tentang Nutrisi pada Ibu Hamil dan Menyusui dalam Pencegahan Stunting - Ximenes, Luvelia Andreja Da Costa Freitas; Mishbahatul, Eka; Indarwati, Retno (Journal of Telenursing (JOTING), 2024)
This study aims to analyse the effect implementing health promotion and education on specific intervention target groups through nutrition in stunting prevention measures. The method used was a systematic review sourced from journals searched through the Scopus database, Ebsco, Web of Science, and Pubmed published in the last 3-year period (2021-2023), regarding the provision of health promotion and education on nutrition as a preventive measure for stunting. Analysis of research results using the PICOS method (Population, Intervention, Compare, Outcome, and Study Design). The results showed that 11 studies met the inclusion criteria. All articles had an experimental study design. The majority of respondents were mothers, breastfeeding mothers, and pregnant women. The results showed the effect of health promotion and nutrition education combined with nutrition on stunting prevention. This journal review concludes that health promotion and nutrition education combined with nutrition affects increasing understanding, attitudes, and behavior in stunting prevention. Keywords: Mother; Pregnant Women, Health Promotion; Health Education; Stunting.